2016
DOI: 10.1007/978-3-319-28887-1
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Consumer Finance Research

Abstract: part of the material is concerned, specifi cally the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfi lms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 406 publications
(431 reference statements)
0
14
0
1
Order By: Relevance
“…There are few family finance research articles with marital instability as an outcome variable (Dew, 2016). That being said, lack of financial resources, as well as other financial stressors, do predict marital dissatisfaction (Archuleta et al, 2011;Conger, Rueter, & Elder, 1999;Dew, 2011;Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007) and divorce (Dew, 2009;cf.…”
Section: Literature Review Empirical Reviewmentioning
confidence: 99%
“…There are few family finance research articles with marital instability as an outcome variable (Dew, 2016). That being said, lack of financial resources, as well as other financial stressors, do predict marital dissatisfaction (Archuleta et al, 2011;Conger, Rueter, & Elder, 1999;Dew, 2011;Gudmunson, Beutler, Israelsen, McCoy, & Hill, 2007) and divorce (Dew, 2009;cf.…”
Section: Literature Review Empirical Reviewmentioning
confidence: 99%
“…Risk tolerance is defined as "the maximum amount of uncertainty someone is willing to accept when making a financial decision" (Grable, 2008 p. 4). Used by many financial professionals to determine appropriate investment choices for their clients, risk tolerance may also influence how individuals invest for their short-and long-term goals, such as a down payment for a house, saving for their children's education, or retirement (Grable, 2008). Research on risk tolerance has repeatedly found young, single, white males with higher income and higher education to have greater risk tolerance (Gibson et al, 2013;Grable, 2000Grable, , 2008Yao et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Used by many financial professionals to determine appropriate investment choices for their clients, risk tolerance may also influence how individuals invest for their short-and long-term goals, such as a down payment for a house, saving for their children's education, or retirement (Grable, 2008). Research on risk tolerance has repeatedly found young, single, white males with higher income and higher education to have greater risk tolerance (Gibson et al, 2013;Grable, 2000Grable, , 2008Yao et al, 2011). Individuals with higher financial knowledge are also more likely to be risk tolerant (Gibson et al, 2013;Grable, 2000Grable, , 2008.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Perilaku dan persepsi tentang seberapa baik pengeloaan keuangan, serta masalah keuangan dan besarnya masalah keuangan berhubungan signifikan PSYCHO IDEA, Tahun 18. No.2, Agustus 2020ISSN 1693-1076(print) ISSN 2654 dengan kepuasan pernikahan (Archuleta, Britt, Tonn, & Grable, 2011;J. P. Dew, 2016;J.…”
Section: Hasilunclassified